2013
DOI: 10.4161/mge.26831
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal targeting by CRISPR-Cas systems can contribute to genome plasticity in bacteria

Abstract: T he clustered regularly interspaced short palindromic repeats (CRISPR) and their associated (Cas) proteins form adaptive immune systems in bacteria to combat phage and other foreign genetic elements. Typically, short spacer sequences are acquired from the invader DNA and incorporated into CRISPR arrays in the bacterial genome. Small RNAs are generated that contain these spacer sequences and enable sequence-specific destruction of the foreign nucleic acids. Occasionally, spacers are acquired from the chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Previously, we have shown that P. atrosepticum contains a native spacer within CRISPR2 (termed C2S6; CRISPR2 Spacer 6) that has perfect complementarity to a chromosomal gene ( eca0560 ) inside an integrative and conjugative element termed horizontally acquired island 2 (HAI2) (28). We previously demonstrated that this spacer was non-functional for interference due to a variant PAM (5′-protospacer-TG-3′) (32,33) (Figure 1A). The lack of interference with C2S6 led us to query whether this -1 PAM point mutation would trigger priming.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that P. atrosepticum contains a native spacer within CRISPR2 (termed C2S6; CRISPR2 Spacer 6) that has perfect complementarity to a chromosomal gene ( eca0560 ) inside an integrative and conjugative element termed horizontally acquired island 2 (HAI2) (28). We previously demonstrated that this spacer was non-functional for interference due to a variant PAM (5′-protospacer-TG-3′) (32,33) (Figure 1A). The lack of interference with C2S6 led us to query whether this -1 PAM point mutation would trigger priming.…”
Section: Resultsmentioning
confidence: 99%
“…Our experimental setup was in serial dilution, which effectively subjects the culture to large daily perturbations in population size, ruling out any mechanism that does not produce an extremely robust coexistence regime. While autoimmunity does not lead to robust host-phage coexistence, it is a common phenomenon across organisms possessing CRISPR immune systems and may have an important effect on the evolution of host immunity in the absence of phage [44][45][46]72].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since autoimmunity and immune loss can both be implemented identically into the equation for defended host they are more easily compared. Autoimmunity could potentially decrease growth rate [44] or cause lethality; we focus on the latter as it will have a stronger effect on the population dynamics [44][45][46]. We implement autoimmunity as an additional death term in the defended host population (α).…”
Section: General Immune Loss Modelmentioning
confidence: 99%
“…Even so, we cannot rule out the relationship between spacers and potential targets because the mutations may occur in proto-spacer regions after the acquisition of CRISPR spacers. 23 Particularly in the phage sequences, escape mutations are more likely to occur as CRISPR is one of the fundamental drivers of phage evolution. 53,54 Therefore, the data can still be used to identify the true origins of the spacers.…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent reports showed that incorporation of self-targeting spacers (targets within the chromosome) is fairly common and completely random, especially in type II CRISPRs. [21][22][23] Although it has been hypothesized that the self-targeting CRISPR system may participate in gene regulation, 24 the complete lack of conservation of self-targeting spacers across species suggests that self-targeting should be regarded as a form of autoimmunity. 25 These spacers may lead to cytotoxicity because of the cleavage function of CRISPR systems, which results in large-scale genomic alterations.…”
Section: Introductionmentioning
confidence: 99%